An Implementation of the Freedom of Learning Concept on Cultural Arts Learning through Babalu Dance: A Case Study of SMP Negeri 3 Batang - Hedianti, Galuh Fatma; Hartono, Hartono; Syakir, Syakir (Catharsis, 2021)
The study has the aim of analyzing critically related to the implementation of the independent learning concept in cultural arts learning. The data collection techniques used in the study were observation, interviews, and document studies. The study used triangulation techniques to maintain the reliability of the data, through data triangulation, source triangulation, and method triangulation. The data analysis technique used in the study is text analysis in choreography context and analysis context in interactive form by following steps namely data collection, data reduction, data presentation, formulating conclusions/ verification. The theoretical formula used in this study is Fisk's theory of the concept of independent learning. The results showed that Babalu Dance learning at SMP Negeri 3 Batang implemented the online freedom of learning concept by utilizing social media platforms namely Whatsapp and Zoom Meeting. The process of cultural arts learning online was reflected in; students could learn at different times and places, student learning was more individual, students had choices in determining how they learnt, the teachers applied project-based learning, the learning was more directed to field experiences, students were more interactive in processing data, teachers could make assessments variously, student involvement, and even though it was online the teacher continued to monitor students in every activity that was carried out.